5-Benzyliden-2-(5-methylthiazol-2-ylimino)thiazolidin-4-ones as Antimicrobial Agents. Design, Synthesis, Biological Evaluation and Molecular Docking Studies - Michelyne Haroun; Christophe Tratrat; Aggeliki Kolokotroni; Anthi Petrou; Athina Geronikaki; Marija Ivanov; Marina Kostic; Marina Sokovic; Alejandro Carazo; Přemysl Mladěnka; Nagaraja Sreeharsha; Katharigatta N. Venugopala; et al. (MDPI AG, 2021)
In this study, we report the design, synthesis, computational and experimental evaluation of the antimicrobial activity, as well as docking studies of new 5-methylthiazole based thiazolidinones. All compounds demonstrated antibacterial efficacy, some of which (1, 4, 10 and 13) exhibited good activity against E. coli and B. cereus. The evaluation of antibacterial activity against three resistant strains, MRSA, P. aeruginosa and E. coli, revealed that compound 12 showed the best activity, higher than reference drugs ampicillin and streptomycin, which were inactive or exhibited only bacteriostatic activity against MRSA, respectively. Ten out of fifteen compounds demonstrated higher potency than reference drugs against a resistant strain of E. coli, which appeared to be the most sensitive species to our compounds. Compounds 8, 13 and 14 applied in a concentration equal to MIC reduced P. aeruginosa biofilm formation by more than 50%. All compounds displayed antifungal activity, with compound 10 being the most active. The majority of compounds showed better activity than ketoconazole against almost all fungal strains. In order to elucidate the mechanism of antibacterial and antifungal activities, molecular docking studies on E. coli Mur B and C. albicans CYP51 and dihydrofolate reductase were performed. Docking analysis of E. coli MurB indicated a probable involvement of MurB inhibition in the antibacterial mechanism of tested compounds while docking to 14α-lanosterol demethylase (CYP51) and tetrahydrofolate reductase of Candida albicans suggested that probable involvement of inhibition of CYP51 reductase in the antifungal activity of the compounds. Potential toxicity toward human cells is also reported.